Isolation of viable Helicobacter pylori in the tonsillar tissues of chronic tonsillitis patients - Wibawa, Tri; Surono, Agus; Widodo, Irianiwati (The Journal of Infection in Developing Countries, 2011)
This item has no abstract available. Use the links below to access the fulll text.<!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman";} > <! [endif] > Background: Helicobacter pylori is a Gram-negative, spiral, microaerophilic bacterium that originally colonizes the human stomach. H. pylori was reported also present in the mouths of both gastric biopsy-positive and gastric biopsy-negative patients, tonsil and adenoid tissues, and middle ear. The objective of this work is to isolate the viable H. pylori which may colonized the tonsillar tissue of chronic tonsillitis patients. Methodology: A total of 19 patients suffering from chronic tonsillitis which were admitted for elective tonsillectomy were included in the study. Specimens of tonsilar tissue were cultured for H. pylori. To confirm the presence of H. pylori, histological examinations were performed using modified Giemsa staining and immunohistochemistry assay. Results: Viable H. pylori were isolated in tonsilar tissue of 3 out of 19 patients (15.7%) suffering from chronic tonsillitis. The result was confirmed using modified Giemsa staining and immunohistochemistry assay. Conclusion: Viable H. pylori colonization in tonsilar tissue of chronic tonsilitis patients may be detected by combination of culture and histological examinations. </sp-->